The Function of FK506-Binding Protein 13 in Protein Quality Control Protects Plasma Cells from Endoplasmic Reticulum Stress-Associated Apoptosis - Jeong, Mini; Jang, Eunkyeong; Choi, Suk San; Ji, Changhoon; Lee, Kyungho; Youn, Jeehee (Frontiers in Immunology, 2017)
Plasma cells are exposed to intense endoplasmic reticulum (ER) stress imposed by enormous rates of immunoglobulin (Ig) synthesis and secretion. Therefore, protein homeostasis is crucial for the survival of plasma cells, but its molecular mechanism remains largely unknown. Here we found marked overexpression of FK506-binding protein 13 (FKBP13) in long-lived plasma cells from autoimmune mice, and investigated its function using a plasmacytoma cell line secreting IgA. FKBP13 expression was induced largely in the lumen of ER in response to treatment with an ER stressor tunicamycin or overexpression of an adaptive unfolded protein response protein X-box binding protein 1 (XBP1). Silencing of FKBP13 expression led to induction of molecules involved in the terminal unfolded protein response and ER stress-associated apoptosis. FKBP13 interacted with Ig, facilitated its ubiquitination, and lowered the extent of ER stress. FKBP13 overexpression caused a significant reduction in secreted IgA in plasmacytoma cells, and FKBP13 knockdown exerted an opposite effect. Rapamycin interfered with the interaction between FKBP13 and IgA and enhanced the amount of secreted IgA. Importantly, the level of FKBP13 was inversely correlated with the amount of secreted antibody in long-lived plasma cells from autoimmune mice. These results suggest that FKBP13 is a marker of long-lived plasma cells and a component of XBP1-dependent ER protein homeostasis. FKBP13 is likely to act as a molecular chaperone that delivers misfolded ER clients, including Ig, to ER-associated degradation, so reducing proteotoxic stress on the plasma cell. Our data reveal a novel cytoprotective role for FKBP13 in long-lived plasma cells occurring at the expense of antibody production.